1989
DOI: 10.1111/j.1365-2184.1989.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin/PCNA immunostaining as an alternative to tritiated thymidine pulse labelling for marking S phase cells in paraffin sections from animal and human tissues

Abstract: Paraffin sections from animal or human tissues fixed in different fixatives were submitted to immunostaining with the mouse monoclonal antibody 19A2, developed by Ogata et al. (1987a) against cyclin/PCNA. Detection of the bound antibody was performed by the indirect method with biotinylated sheep antibody and streptavidin‐biotin‐peroxidase complexes. No, or faint, nuclear staining was seen in material fixed in ethanol, Bouin, Bouin‐Hollande, Carnoy or formaldehyde, whereas readily detectable immunocytochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
1
7

Year Published

1993
1993
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 19 publications
3
95
1
7
Order By: Relevance
“…This is probably due to the fact that the immunoreactivity of PCNA is affected by factors such as a type of antibodies and of fixatives, a fixation condition and a staining procedure against PCNA. For example, there is a report that whereas monoclonal antibody 19A2 exclusively recognize S-phase cells in methanol-fixed tissues, it reacts with cycling cells in formaldehyde-fixed tissues (10). In contrast, Landberg and Roos (17) did not find such staining characteristics for 19A2 in samples fixed in methanol.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is probably due to the fact that the immunoreactivity of PCNA is affected by factors such as a type of antibodies and of fixatives, a fixation condition and a staining procedure against PCNA. For example, there is a report that whereas monoclonal antibody 19A2 exclusively recognize S-phase cells in methanol-fixed tissues, it reacts with cycling cells in formaldehyde-fixed tissues (10). In contrast, Landberg and Roos (17) did not find such staining characteristics for 19A2 in samples fixed in methanol.…”
Section: Discussionmentioning
confidence: 96%
“…At least two different populations of PCNA have been identified (3,10,20,22,24). It was reported that methanol fixation extracted free PCNA, and that in 3T3 cells, 20-30% of the total PCNA remained even after methanol fixation (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNA expression is therefore correlated with the cell cycle. Several authors have suggested this staining as an alternative for thymidine pulse labelling, especially in pre-existing fixed or frozen materials (Galand et al, 1989;Kawakita et al, 1992). We are aware that PCNA staining gives an overestimation of proliferation when compared with 'classical' thymidine incorporation because all cells, except those in Go state, are stained.…”
Section: Discussionmentioning
confidence: 99%
“…In the P3 forebrain, a significant level of m-Msi-1 expression was observed in the tightly packed round cells in the SVZ, which was composed of PCNApositive proliferating cells (Fig. 1 D,E) (Galand and Degraef, 1989), near the anterior part of the lateral ventricle (SVZa), and was also detected in the migratory pathway toward the olfactory bulb (Fig. 1 B).…”
Section: M-msi-1 Expression In the Svz Of The Forebrainmentioning
confidence: 99%